Metodologia para medição de temperatura durante o fresamento de metais utilizando termografia direcional espectral - Matheus de Oliveira Moreira (2021)
Temperature monitoring during the machining of metals is a way of understanding and controlling the cutting process. The use of infrared-based devices during the milling of metals has advantages, such as lower response time and the possibility of monitoring temperature profile. However, the software applied to commercial thermal imagers uses the simplified model of the diffuse-gray surface. The scientific literature shows that the emissivity of metallic surfaces depends on temperature, spectrum, and direction. Despite that, the studies about monitoring temperature during machining of metals often neglect those dependencies. This work proposes a methodology to estimate the temperature of metallic surfaces during face milling using thermal imagers. This procedure contains a step for the estimation of the metallic surface emissivity, taking into account the dependence on temperature, spectrum, and direction. An experimental approach was used to measure the variables that were applied to the post-processing routine. The mathematical model was iterative and based on a spectral-directional formulation of radiation heat transfer. AISI H13 steel was used as work material. The estimates of emissivity varied from 0,12 to 0,20 in the spectral band of 7,5 µm to 13 µm and temperature interval of 50 °C to 250 °C. The workpiece temperature during milling was estimated for twelve different cutting conditions. The estimates ranged from 100 °C to 188 °C. The results obtained using the proposed procedure were compared with the values from three alternative methods. These methods neglect the influences of the spectrum and temperature on the emissivity. Relative to the estimates from the directional-spectral procedure proposed in this work, the difference was up to 41%. It demonstrated that attention must be given to the temperature estimation procedure.